The Role of Health Savings Accounts in Enhancing Economic Security for Low-Income Families - Assaf Filfilan; Ahmed Shawdari; Dr. Mohammed Ibrahim Alattas (The Bioscan, 2024)
In the pursuit of improving economic security for low-income families, Health Savings Accounts (HSAs) have emerged as a pressing topic of interest due to their potential role in financial empowerment and poverty alleviation. This study seeks to evaluate the effectiveness of HSAs as a tool for enhancing economic security among economically vulnerable populations. Utilizing a survey-based methodology, data was collected from economists in Saudi Arabia to gauge their perceptions of HSAs' benefits, challenges, and the role of supportive financial services. The findings reveal a mixed perception of HSAs' effectiveness, with significant barriers identified, such as insufficient financial literacy and inadequate disposable income among low-income families. The study highlights the need for integrated financial strategies that include policy-driven incentives, extensive financial education, and digital platform integration to enhance the accessibility and utility of HSAs. By addressing the structural limitations and fostering strategic integration with broader financial services, HSAs can be transformed into potent instruments for economic resilience and empowerment. The research provides actionable insights for policymakers and stakeholders, contributing to the dialogue on effective strategies for fostering financial inclusion and economic stability for low-income families.